Ultra-low specific on-resistance vertical double-diffused metal-oxide semiconductor with a high-k dielectric-filled extended trench - 王沛 罗小蓉 蒋永恒 王琦 周坤 吴丽娟 王骁玮 蔡金勇 罗尹春 范叶 胡夏融 范远航 魏杰 张波 (Chinese physics B, 2013)
An ultra-low specific on-resistance trench gate vertical double-diffused metal-oxide semiconductor with a high-k dielectric-filled extended trench（HK TG VDMOS） is proposed in this paper.The HK TG VDMOS features a high-k（HK） trench below the trench gate.Firstly,the extended HK trench not only causes an assistant depletion of the n-drift region,but also optimizes the electric field,which therefore reduces Ron,sp and increases the breakdown voltage（BV）.Secondly,the extended HK trench weakens the sensitivity of BV to the n-drift doping concentration.Thirdly,compared with the superjunction（SJ） vertical double-diffused metal-oxide semiconductor（VDMOS）,the new device is simplified in fabrication by etching and filling the extended trench.The HK TG VDMOS with BV = 172 V and Ron,sp = 0.85 mΩ·cm2 is obtained by simulation;its Ron,sp is reduced by 67% and 40% and its BV is increased by about 15% and 5%,in comparison with those of the conventional trench gate VDMOS（TG VDMOS） and conventional superjunction trench gate VDMOS（SJ TG CDMOS）.